Reaction-based fluorogenic probes for detecting protein cysteine oxidation in living cells - Renan B. Ferreira; Ling Fu; Youngeun Jung; Jing Yang; Kate S. Carroll (Nature Communications, 2022)
Fluorogenic detection of H2O2 in cells is established, but equivalent tools to monitor its cellular targets remain in their infancy. Here authors develop fluorogenic probes for detecting cysteine sulfenic acid, a redox modification inextricably linked to H2O2 signalling and oxidative stress.